Bucharest-Ilfov Region – Between Economic and Social Convergence and Divergence - Catalina Mihaela Badoiu (CES Working Papers, 2014)
This paper aims to highlight the main economic disparities between the developing regions of Romania, during the 2005-2011/2012 period. We will focus on the Bucharest-Ilfov region, which differs both in terms of population density, and the galloping economic growth, relative to other regions. In terms of the convergence-divergence analysis, it will be based on key indicators, such as the factors that led to increased inter-regional divergence and to what extent the differences between regions were reduced in the analyzed period.
Keywords: F30; F50; O52; 330; Regional disparities; Convergence; Concentration; Distribution analysis Romania